Gestão e inclusão social na escola pública: uma questão de qualidade e humanização - Ferreira, Sonia Aparecida Felipe (2009)
We know that the education is of odd importance for the formation of the citizenship. However, young and adolescent children with report of difficulty of the social education adjustment and with difficulty of learning of the school contents, they need appropriate effective actions from these public's characteristics. The present work has for purpose to approach the paper of the school, of the student, of the educator and of the family, in the process of the students' school and social inclusion with special educational needs. He/she will put emphasis that those labeled students, known as Attended Freedom (LA), that had passage in the House Foundation or in prison. The traveled road was made by the study of aspects of a located public school in the periphery of the city of Mauá in which we came across a quite arduous reality, with many confronts - from subjects of School Administration the lack of family structure. Due to the found reality, we can infer that is done necessary an urgent reformation of the school curriculum, investments of the publish politics in the education of Base, improvement of the work conditions in the public schools and teachers' of the net continuous formation, seeking that these can develop pedagogic competence in your multiples aspects. That managers and educators human beings, ethical, reflexive, competent and know how to work with the human diversity, doing of this, a possibility of mutual growth. Like this, it will be possible to conquer a world for ALL, where the inclusion can be really true